Propuesta metodológica "ADD" para mejorar la producción de textos escritos en francés de los estudiantes del tercer año de idiomas de la facultad de educación y ciencias de la comunicación - Anticona Sandoval, Rosa Ubaldina (2019)
ABSTRACT The research is to establish the relationship between the methodological proposal "ADD” (Before, During and After) and the production improvement of written texts in French of the students of the Professional Career of Secondary Education majoring in Languages, French area, of the Faculty of Education and Communication Sciences of the National University of Trujillo. The purpose of this study was to determine the effectiveness of the proposal, to do so, the knowledge processes of the textual production was specifically described according to the strategy proposed. This research is of quasi-experimental type; the design was descriptive and correlational. The sample was based on 27 students of the third year in French Subject II – 2012 of the Language Career who were selected by taking into consideration the non-probabilistic design due to being of direct election. In the process, a pre-test was applied; then, the methodological proposal "ADD" was applied in 16 sessions and finally a post test was developed. For the qualification of the questionnaires, the Likert scale was used which confirmed, through the statistical measurement, the direct significant relationship of the applied strategy.